THE ASSOCIATION BETWEEN PHYSICAL ACTIVITY, LEVEL OF STRESS, AND ECONOMIC STATUS WITH THE NUTRITIONAL STATUS AMONG ADOLESCENT FEMALES IN COASTAL REGIONS - Kadek Ayu Dwi Wulandari; I I Putu Sudayasa; Susanty, Sri (The Indonesian Journal of Public Health, 2025)
Introduction: Adolescent girls belong to a population that is particularly susceptible to dietary deficiencies. The nutritional issues experienced by adolescents significantly affect the well-being of both present and future generations, as well as the overall economic and health of the nation. Various factors have been found related to nutritional issues and have a significant impact on the well-being of adolescent girls by approximately 28.4%. Aims: The purpose of this study is to determine the relationship between physical activity status, levels of stress and economic status with the nutritional status of adolescent girls in coastal regions. Methods: This study employs an analytical observational research design using a cross-sectional method. The independent factors consist of physical activity, level of stress, and economic position, whereas the dependent variable pertains to nutritional status as measured by BMI. The study included a sample of 176 adolescent girls residing in the coastal region. The participants were chosen using the stratified random sampling method. Results: Research showed that 109 (61.9%) respondents had good nutritional status, 40 (22.7%) were undernourished and 27 (15.3%) were over nourished. Based on statistical tests, p-physical activity (p=0.000), level of stress (p=0.000), and economic status (p=0.000) were obtained. Conclusions: Physical activity, level of stress, and economic status have a relationship with the nutritional status of adolescent girls in the coastal regions.